The Degree of Practice of Department Managers in Government Agencies in the Kingdom of Saudi Arabia for Excellence Management According to the European Foundation for Quality Management (EFQM) Model and Ways to Develop It: The Ministry of Interior as a Case Study (International Journal of Financial, Administrative and Economic Sciences, 2026)
The study aimed to identify the degree of practice of department managers in government agencies affiliated with the Ministry of Interior in Al-Madinah Al-Munawwarah in applying Excellence Management according to the European Foundation for Quality Management (EFQM) model, as well as to explore ways to develop the application of this model in government agencies. The study adopted the descriptive survey method as it is appropriate for the nature of the study. The researcher used a questionnaire as a tool to collect the responses of the study sample, and the data were analyzed using the Statistical Package for Social Sciences (SPSS).The study population consisted of all department managers in the government agencies affiliated with the Ministry of Interior in Al-Madinah Al-Munawwarah, totaling (60) managers, while the study sample consisted of (52) managers.The results of the study showed that the level of practice of department managers in applying Excellence Management according to the EFQM model was high. The purpose, vision, and strategy dimension recorded a high level with a mean of (3.48). The organizational and leadership culture dimension also showed a high level with a mean of (3.59), while the stakeholder engagement dimension recorded a high level with a mean of (3.54). In addition, the creating sustainable value criterion showed a high level with a mean of (3.53). Similarly, the driving performance and transformation dimension recorded a high level with a mean of (3.58), while the stakeholders’ perceptions dimension recorded a high level with a mean of (3.57), and the strategic and operational performance dimension also showed a high level with a mean of (3.56).Based on the findings, the researcher recommended several recommendations, the most important of which are enhancing the requirements for applying institutional excellence management in the government agencies affiliated with the Ministry of Interior in Al-Madinah Al-Munawwarah by providing modern technological systems that contribute to improving the quality of government services and developing institutional performance. The study also recommended developing the leadership and administrative capabilities of department managers through specialized training programs in leadership and institutional excellence, as well as adopting initiatives and awards for institutional excellence to motivate outstanding performance and promote a culture of excellence within government agencies.
Keywords: Degree of Practice; Excellence Management; European Foundation for Quality Management (EFQM); Government Agencies; Ministry of Interior; Al-Madinah Al-Munawwarah